Redox sintering method of interconnected sample based on copper paste and electronic device
By applying pressure and ladder heating in the oxidation and reduction sintering method, the problem of poor mechanical properties in the sample sintering process of interconnect samples significantly improves the mechanical shear strength of the joints and the density of micro -tissue.
Patent Information
- Application Number
- CN202411476252.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-28
AI Technical Summary
In the prior art, interconnected samples have poor mechanical properties during sintering, especially the lack of pressure during the oxidative sintering step, resulting in low density.
Adopting copper -based oxidation and reducing sintering methods, pressure is applied during the process of oxidation and reducing sintering, and the mechanical shear strength of the joint is enhanced by gradient heating.
By applying pressure and gradient heating, the mechanical properties of interconnected samples are significantly improved, especially the mechanical shear strength of the joints, which improves the density of micro -organizations.
Smart Images

Figure CN119368745A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electronic products, and in particular to a redox sintering method of an interconnection sample based on copper paste and an electronic device. Background Art
[0002] In the related technology, the process of preparing interconnected samples usually includes two steps: oxidation sintering and reduction sintering. During the sintering process, the current sintering technology does not apply pressure to the interconnected samples, so that the microstructure density is low and the mechanical properties of the joints are good. A small number of technologies apply pressure to the interconnected samples during the reduction sintering process. Although this has a certain improvement on the microstructure density, the effect is not good. Summary of the invention
[0003] The present invention aims to solve or improve the technical problem of poor mechanical properties of interconnected samples during sintering in the prior art.
[0004] The first aspect of the present invention is to provide a redox sintering method for an interconnection sample based on copper paste, comprising: dissolving the raw materials of the copper paste in an organic solvent to obtain a copper paste slurry; preparing an interconnection sample by means of an upper substrate, a lower substrate and the copper paste slurry; applying pressure to the interconnection sample on the upper substrate in the direction of the lower substrate; heating the interconnection sample under pressure at a first preset rate, and after reaching a first preset temperature, keeping the temperature for a first preset time, and then cooling the interconnection sample to room temperature; in a reducing gas environment, heating the interconnection sample at room temperature at a second preset rate, and after reaching the second preset temperature, keeping the temperature for a second preset time, and then heating at a third preset rate, and after reaching the third preset temperature, keeping the temperature for a third preset time.
[0005] The sintering method provided by the present invention applies pressure during both oxidation sintering and reduction sintering. Compared with conventional pressure-free sintering or pressure only applied during reduction sintering, pressure is also applied to the interconnected sample during the oxidation sintering step, so that the copper paste and the substrate structure can be in close contact. In addition, the present invention does not directly perform reduction sintering after oxidation sintering, but first cools the interconnected sample to room temperature, and then slowly heats it to the sintering temperature of reduction sintering, and heats it in a gradient during the reduction sintering process, which can greatly improve the mechanical shear strength of the joint.
[0006] In some technical schemes, optionally, the raw materials of the copper paste include micron-sized copper particles and nano-sized copper particles, the diameter of the micron-sized copper particles is greater than or equal to 1 μm and less than or equal to 100 μm, for example, 10 μm, 20 μm, etc., and the diameter of the nano-sized copper particles is greater than or equal to 1 nm and less than or equal to 100 nm, for example, 10 nm, 20 nm, etc.
[0007] In this technical solution, micron-sized copper particles and nano-sized copper particles are used as raw materials for copper paste, which can not only ensure the density of the microstructure, improve the mechanical shear strength of the connection joints of the copper paste interconnected samples, but also reduce production costs.
[0008] In some technical solutions, optionally, the mass ratio of micrometer-sized copper particles to nanometer-sized copper particles is greater than or equal to 3 and less than or equal to 5.
[0009] In this technical solution, too many micron-sized copper particles result in low microstructure density and poor mechanical shear strength of the connecting joints. Too many nano-sized copper particles do not significantly improve the microstructure density, but greatly increase the production cost. Therefore, it is most appropriate to control the mass ratio of micron-sized copper particles to nano-sized copper particles to be greater than or equal to 3 and less than or equal to 5. For example, the mass ratio of micron-sized copper particles to nano-sized copper particles is 4.
[0010] In some technical schemes, optionally, the step of preparing an interconnection sample through an upper substrate, a lower substrate and a copper paste slurry includes: positioning the lower substrate, brushing the copper paste slurry onto the upper surface of the lower substrate, and then placing the upper substrate on the copper paste slurry to obtain an interconnection sample.
[0011] In some technical solutions, optionally, the step of applying pressure to the interconnected sample specifically includes: placing the interconnected sample in a fixture, and applying pressure to the interconnected sample through the fixture.
[0012] In this technical solution, the interconnected sample can be placed in a fixture, and pressure can be applied to the interconnected sample by the fixture, so that the density of the connection joint can be higher. Of course, other pressure application methods can also be adopted, such as applying pressure to the upper surface of the interconnected sample by a spring.
[0013] In some technical solutions, optionally, in the step of applying pressure to the interconnected sample, the applied pressure is greater than or equal to 100N and less than or equal to 1000N. Optionally, the applied pressure is greater than or equal to 300N and less than or equal to 500N, for example 300N, 400N or 500N.
[0014] In this technical solution, the pressure applied to the interconnected samples is controlled. On the one hand, this can make the interconnected samples have better tissue density and higher mechanical properties during the sintering process. On the other hand, it can also prevent the copper paste from being deformed due to excessive pressure.
[0015] In some technical schemes, optionally, the first preset rate is greater than or equal to 1°C / s and less than or equal to 2°C / s; the first preset temperature is greater than or equal to 280°C and less than or equal to 320°C; the first preset time is less than or equal to 40min; the second preset rate is greater than or equal to 1°C / s and less than or equal to 2°C / s; the second preset temperature is greater than or equal to 25°C and less than or equal to 35°C; the second preset time is greater than or equal to 20min and less than or equal to 2h; the third preset rate is greater than or equal to 1°C / s and less than or equal to 2°C / s; the third preset temperature is greater than or equal to 200°C and less than or equal to 300°C; the third preset time is less than or equal to 20min.
[0016] In this technical solution, the mechanical properties of the connection joint can be further improved by controlling parameters such as the temperature change rate, the holding temperature and the holding time during the oxidation sintering and reduction sintering processes.
[0017] In some technical solutions, optionally, the reducing gas includes formic acid gas.
[0018] In this technical solution, formic acid gas has good reducing properties and can further reduce the oxide layer on the surface of the copper particles, thereby improving the mechanical properties of the connection joint.
[0019] In some technical schemes, optionally, the redox sintering method of the interconnection sample based on copper paste also includes: after keeping warm for a third preset time, cooling the interconnection sample to a fourth preset temperature at a fourth preset rate; the fourth preset rate is greater than or equal to 1°C / s and less than or equal to 2°C / s, and the fourth preset temperature is greater than or equal to 30°C and less than or equal to 50°C.
[0020] In this technical solution, after the reduction sintering step, the interconnected samples are cooled to make the structural properties of the connection joint more stable.
[0021] In some technical solutions, optionally, the organic solvent includes terpineol.
[0022] In this technical solution, pinene alcohol can fully dissolve copper particles and improve the joint connection strength of the interconnected samples.
[0023] The technical solution of the second aspect of the present invention provides an electronic device, including an interconnection sample, which is prepared by the redox sintering method of the copper paste-based interconnection sample provided by any technical solution of the first aspect of the present invention.
[0024] Since the electronic device provided by the present invention includes an interconnection sample, and the interconnection sample is prepared by the redox sintering method of the interconnection sample based on copper paste provided by any technical solution of the first aspect, the electronic device of the present invention has all the beneficial effects of the redox sintering method of the interconnection sample based on copper paste provided by any technical solution of the first aspect of the present invention.
[0025] Additional aspects and advantages of the present invention will become apparent in the following description or may be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The above and / or additional aspects and advantages of the embodiments of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which: Figure 1 A flow chart of a method for preparing a redox sintering interconnection sample based on a copper paste provided by an embodiment of the present invention is shown; Figure 2 A flow chart showing a preparation method of a redox sintering method for an interconnection sample based on a copper paste provided in a comparative example of the present invention is shown; Figure 3 shows a microstructure diagram of an interconnection sample provided by an embodiment of the present invention; Figure 4 A schematic diagram showing the preparation principle of the interconnection sample of the present invention is shown; Figure 5 A diagram showing the structure of a mounting fixture for interconnection samples of the present invention is shown; Figure 6 A temperature-time relationship diagram of a redox sintering method for interconnection samples based on copper paste provided by an embodiment of the present invention is shown; Figure 7 A schematic diagram showing the state of copper particles and organic solvents before mixing provided by an embodiment of the present invention is shown; Figure 8 A schematic diagram showing a state after copper particles provided by an embodiment of the present invention are mixed with an organic solvent; Fig. 9 A structural diagram of an interconnection sample provided by an embodiment of the present invention is shown; Fig.10 A schematic structural diagram of an electronic device provided by an embodiment of the present invention is shown.
[0027] in, Figure 4 , Figure 5 , Figures 7 to 10 The corresponding relationship between the reference numerals and component names in the figure is: 1 electronic device, 2 interconnection sample, 21 lower substrate, 22 upper substrate, 23 interconnection layer, 3 printing steel plate, 34 copper paste printing hole, 4 scraper, 5 copper paste slurry, 6 fixture, 61 upper fixture, 62 lower fixture, 7 spring, 81 bolt, 82 nut, 91 copper particles, 92 organic solvent. DETAILED DESCRIPTION
[0028] In order to more clearly understand the above aspects, features and advantages of the embodiments of the present invention, the embodiments of the present invention are further described in detail below in conjunction with the accompanying drawings and specific implementation methods. It should be noted that the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.
[0029] In the following description, many specific details are set forth to facilitate a full understanding of the embodiments according to the present invention. However, the embodiments according to the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the embodiments according to the present invention is not limited to the specific embodiments disclosed below.
[0030] Embodiment 1
[0031] like Figure 1 As shown, the redox sintering method of the interconnection sample based on copper paste provided by the present invention comprises the following steps: S102: dissolving raw materials of the copper paste in pinene alcohol to obtain a copper paste slurry; S104: preparing an interconnection sample by using an upper substrate, a lower substrate and a copper paste slurry; S106: applying pressure to the interconnected sample on the upper substrate in the direction of the lower substrate; S108: The interconnected sample under pressure is heated at a heating rate of 1°C / s. After reaching 300°C, the temperature is kept at this temperature for 40 minutes. The interconnected sample is then cooled to room temperature. In a formic acid gas environment, the temperature is kept at 30°C for 30 minutes. The temperature is then increased at a heating rate of 1°C / s. After reaching 250°C, the temperature is kept at this temperature for 20 minutes.
[0032] Comparative Example 1 like Figure 2 As shown, the redox sintering method of the interconnection sample based on copper paste provided in this comparative example comprises the following steps: S202: dissolving raw materials of the copper paste in pinene alcohol to obtain a copper paste slurry; S204: preparing an interconnection sample by using an upper substrate, a lower substrate and a copper paste slurry; S206: heating the interconnection sample at a heating rate of 1°C / s, and after reaching 300°C, keeping the temperature for 40 minutes, and then cooling the interconnection sample to room temperature; S208: applying pressure to the interconnected sample on the upper substrate in a direction toward the lower substrate; S210: In a formic acid gas environment, the interconnected sample under pressure was heated at a heating rate of 1°C / s. After reaching 30°C, it was kept warm for 10 minutes. Then, the temperature was increased at a heating rate of 1°C / s. After reaching 250°C, it was kept warm for 20 minutes.
[0033] Comparative Example 2 There is a difference in the sintering process of this comparative example and Example 1, step S108. In this comparative example 2, the interconnected sample under pressure is heated at a heating rate of 1°C / s, and after reaching 300°C, it is kept warm for 40 minutes, and then cooled to 250°C at a cooling rate of 1°C / s in a formic acid gas environment, and then kept warm for 20 minutes.
[0034] Comparative Example 3 There is a difference in the sintering process of this comparative example and embodiment one, step S108. In this comparative example three, the interconnected sample under pressure is heated at a heating rate of 1°C / s. After reaching 300°C, it is kept warm for 40 minutes, and then the interconnected sample is cooled to room temperature. In the environment of formic acid gas, the interconnected sample at room temperature is heated at a heating rate of 1°C / s. After reaching 250°C, it is kept warm for 20 minutes.
[0035] The following is a test of the joint mechanical shear strength of the interconnected samples prepared in Example 1 and Comparative Examples 1 to 3, and the test standard is GB / T 1450.1-Test method for shear strength between fiber reinforced plastic layers. The test results are shown in Table 1 below: test Shear Strength Embodiment 1 28MPa Comparative Example 1 20MPa Comparative Example 2 22MPa Comparative Example 3 23MPa Table 1 It can be seen from Table 1 that the interconnection sample 2 prepared in Example 1 of the present invention has good stability and higher shear strength. The cross-sectional structure diagram of the interconnection sample 2 prepared in Example 1 is as follows: Figure 3 As shown, Figure 3 In the figure, (a), (b) and (c) are cross-sectional microstructures at three different scales. The structure of interconnection sample 2 is shown in Fig. 9 As shown, in comparative example 1, no pressure was applied to the interconnected sample 2 during the oxidation sintering process, and the structural organizations of the two could not be in close contact, resulting in a low mechanical shear strength of the joint. In comparative example 2, the interconnected sample 2 was not lowered to room temperature after oxidation sintering, and in comparative example 3, no gradient heating was performed during the reduction sintering process, both of which resulted in a low mechanical shear strength of the joint.
[0036] Another embodiment of the present invention provides a redox sintering method for an interconnection sample based on copper paste, specifically, the raw materials of the copper paste are dissolved in an organic solvent 92 to obtain a copper paste slurry 5; an interconnection sample 2 is prepared by an upper substrate 22, a lower substrate 21 and the copper paste slurry 5; pressure is applied to the interconnection sample 2 on the upper substrate 22 in the direction of the lower substrate 21; the interconnection sample 2 under pressure is heated at a first preset rate, and after reaching a first preset temperature, the temperature is kept for a first preset time, and then the interconnection sample 2 is cooled to room temperature; in a reducing gas environment, the room temperature interconnection sample 2 is heated at a second preset rate, and after reaching a second preset temperature, the temperature is kept for a second preset time, and then the temperature is heated at a third preset rate, and after reaching a third preset temperature, the temperature is kept for a third preset time. Among them, Figure 7 shows the state of copper particles 91 before being dissolved in organic solvent 92. Figure 8 The state of the copper particles 91 after being dissolved in the organic solvent 92 is shown. The sintering method provided by the present invention applies pressure during both oxidation sintering and reduction sintering. Compared with the conventional pressure-free sintering or pressure only during reduction sintering, pressure is also applied to the interconnection sample 2 during the oxidation sintering step, so that the copper paste can be in close contact with the structure of the substrate. In addition, the present invention does not directly perform reduction sintering after oxidation sintering, but first cools the interconnection sample 2 to room temperature, and then slowly heats it to the sintering temperature of reduction sintering, and heats it in a gradient during the reduction sintering process, which can greatly improve the mechanical shear strength of the joint.
[0037] In some embodiments, optionally, the raw materials of the copper paste include micron-sized copper particles and nano-sized copper particles, the diameter of the micron-sized copper particles is greater than or equal to 1 μm and less than or equal to 100 μm, optionally, the diameter of the micron-sized copper particles is greater than or equal to 20 μm and less than or equal to 50 μm, for example, 20 μm, 30 μm or 50 μm, and the diameter of the nano-sized copper particles is greater than or equal to 1 nm and less than or equal to 100 nm, optionally, the diameter of the nano-sized copper particles is greater than or equal to 20 nm and less than or equal to 50 nm, for example, 20 nm, 30 nm or 50 nm.
[0038] In this embodiment, micron-sized copper particles and nano-sized copper particles are used as raw materials for the copper paste, which can not only ensure the density of the microstructure, but also improve the mechanical shear strength of the connecting joints of the interconnection sample 2 and reduce the production cost.
[0039] In some embodiments, optionally, the mass ratio of the micron-sized copper particles to the nano-sized copper particles is greater than or equal to 3 and less than or equal to 5.
[0040] In this embodiment, too many micron-sized copper particles result in low microstructure density and poor mechanical shear strength of the connecting joint. Too many nano-sized copper particles do not significantly improve the microstructure density, but greatly increase the production cost. Therefore, it is most appropriate to control the mass ratio of micron-sized copper particles to nano-sized copper particles to be greater than or equal to 3 and less than or equal to 5. For example, the mass ratio of micron-sized copper particles to nano-sized copper particles is 4.
[0041] In some embodiments, optionally, the step of preparing the interconnection sample 2 by the upper substrate 22, the lower substrate 21 and the copper paste slurry 5 includes: positioning the lower substrate 21, brushing the copper paste slurry 5 onto the upper surface of the lower substrate 21, and then placing the upper substrate 22 on the copper paste slurry 5 to obtain the interconnection sample 2.
[0042] In some embodiments, optionally, the step of applying pressure to the interconnected sample 2 specifically includes: placing the interconnected sample 2 in a fixture 6 , and applying pressure to the interconnected sample 2 through the fixture 6 .
[0043] In this embodiment, the interconnected sample 2 can be placed in the fixture 6, and pressure can be applied to the interconnected sample 2 by the fixture 6, so that the density of the connection joint can be higher. Of course, other pressure application methods can also be adopted, such as applying pressure to the upper surface of the interconnected sample 2 by a spring.
[0044] In some embodiments, optionally, in the step of applying pressure to the interconnected sample 2 , the applied pressure is greater than or equal to 100 N and less than or equal to 1000 N. Optionally, the applied pressure is greater than or equal to 300 N and less than or equal to 500 N, for example, 300 N, 400 N or 500 N.
[0045] In this embodiment, the pressure applied to the interconnection sample 2 is controlled. On the one hand, the interconnection sample 2 can have better tissue density and higher mechanical properties during the sintering process. On the other hand, it can also prevent the copper paste from being deformed due to excessive pressure.
[0046] In some embodiments, optionally, the first preset rate is greater than or equal to 1°C / s and less than or equal to 2°C / s, for example, 1°C / s, 1.5°C / s or 2°C / s; the first preset temperature is greater than or equal to 280°C and less than or equal to 320°C, for example, 280°C, 300°C or 320°C; the first preset time is less than or equal to 40 minutes, for example, 30 min; the second preset rate is greater than or equal to 1℃ / s and less than or equal to 2℃ / s, for example, 1℃ / s, 1.5℃ / s or 2℃ / s; the second preset temperature is greater than or equal to 25℃ and less than or equal to 35℃, for example, 28℃, 30℃ or 32℃; the second preset time is greater than or equal to 20min and less than or equal to 2h, for example, 40min or 60min; the third preset rate is greater than or equal to 1℃ / s and less than or equal to 2℃ / s, for example, 1℃ / s, 1.5℃ / s or 2℃ / s; the third preset temperature is greater than or equal to 200℃ and less than or equal to 300℃, for example, 240℃, 260℃ or 280℃; the third preset time is less than or equal to 20min, for example, 10min.
[0047] In this embodiment, the mechanical properties of the connection joint can be further improved by controlling parameters such as the temperature change rate, the holding temperature, and the holding time during the oxidation sintering and reduction sintering processes.
[0048] In some embodiments, optionally, the reducing gas includes formic acid gas.
[0049] In this embodiment, the formic acid gas has good reducing properties and can further reduce the oxide layer on the surface of the copper particles 91 to improve the mechanical properties of the connection joint.
[0050] In some embodiments, optionally, the redox sintering method of the interconnect sample based on copper paste also includes: after keeping warm for a third preset time, cooling the interconnect sample 2 to a fourth preset temperature at a fourth preset rate; the fourth preset rate is greater than or equal to 1°C / s and less than or equal to 2°C / s, and the fourth preset temperature is greater than or equal to 30°C and less than or equal to 50°C.
[0051] In this embodiment, after the reduction sintering step, the interconnection sample 2 is cooled to make the structural properties of the connection joint more stable.
[0052] In some embodiments, optionally, the organic solvent 92 includes terpineol.
[0053] In this embodiment, pinene alcohol can fully dissolve the copper particles 91 and improve the joint connection strength of the interconnection sample 2 .
[0054] Another embodiment of the present invention provides a redox sintering method for interconnection samples based on copper paste, the method comprising the following steps: Step 1, preparing copper particle copper paste: mixing the micron-sized and nano-sized copper particles obtained by atomization with an organic solvent, wherein the mass percentage of the micron-sized and nano-sized copper particles is 80:20, and the mass percentage of pure copper particles in the copper paste is 75%-85%; Step 2: Prepare the corresponding copper paste interconnection sample 2: Figure 4 and Figure 5 As shown, the printed steel plate 3 is placed on the placement table, the lower substrate 21 is placed under the printed steel plate 3, and the lower substrate 21 is fixed at a specified position through the edge positioning hole of the printed steel plate 3. Then, the copper paste slurry 5 obtained above is applied to the corresponding lower substrate 21 from the position of the copper paste printing hole 34 by a scraper 4 through a screen printing method, and the copper paste slurry 5 is repeated to evenly distribute the copper paste slurry 5 and is in the same plane as the upper plane of the printed steel plate 3. The printed steel plate 3 is gently withdrawn, and finally the upper substrate 22 is placed on the lower substrate 21 accordingly; the printing thickness of the copper paste slurry 5 depends on the thickness of the printed steel plate 3, and the thickness of the printed steel plate 3 is 0.05mm-0.2mm; Step 3, preparing the fixture 6: using the modeling software, selecting the size and material of the fixture 6, and preparing a suitable fixture 6, wherein the material of the fixture 6 is steel; Step 4: Assemble the pressurized interconnection sample 2 to be sintered: Figure 5 As shown, the interconnection sample 2 is composed of an upper substrate 22, a lower substrate 21 and an interconnection layer 23. The interconnection sample 2 is placed in an upper clamp 61 and a lower clamp 62. The clamp 6 is assembled by nuts 82 and bolts 81. Pressure is applied to the interconnection sample 2, wherein a certain pressure is provided by a spring 7 in the clamp 6. Step 5, oxidation sintering: placing the assembled interconnection sample 2 in a sintering furnace, heating it from room temperature at a rate of 1°C / s-2°C / s, reaching the oxidation temperature for sintering oxidation process, the temperature is 300°C, and the continuous holding time is 0min-40min; Step 6: Reduction sintering: Figure 6 As shown, the interconnection sample 2 assembled above is placed in a sintering furnace, and reducing gas is introduced after the air is removed to prevent the presence of oxygen in the cavity from being oxidized again. The reducing gas reduces the oxide film of the copper particles to promote the sintering process. The temperature is raised at a rate of 1°C / s-2°C / s, first to a standard sintering temperature of 300°C, and the sintering time is kept at a temperature of 20 minutes, and then the temperature is lowered to 250°C at a rate of 1°C / s-2°C / s, and the reducing gas is removed after 1 to 20 minutes, and finally the temperature is lowered at a rate of 1°C / s-2°C / s to obtain the sample. Of course, the temperature can also be raised at a rate of 1°C / s-2°C / s first to a standard sintering temperature of 300°C, and then oxidation and reduction sintering are performed at 300°C at the same time, and finally the temperature is lowered at a rate of 1°C / s-2°C / s to obtain the sample.
[0055] Step 7, cooling: cool the interconnected sample 2 from high temperature at a rate of 1°C / s-2°C / s, and reduce the temperature to 30°C. First, remove the reducing gas, and then fill in hot nitrogen to keep the pressure balance in the sintering furnace cavity to ensure that the sintering furnace can be opened smoothly. The cooling time lasts for 30min-50min. Step eight, remove the fixture 6 to obtain the interconnection sample 2, open the sintering furnace cavity, obtain the assembled interconnection sample 2, and remove the fixture 6 to obtain the interconnection sample.
[0056] In step 1, mixed micron-sized and nano-sized copper particles are used, small particles fill the pores of large particles to promote sintering, and the organic solvent 92 is pinene alcohol.
[0057] Among them, in step 2, the thickness of the printed steel plate 3 determines the thickness of the copper paste slurry 5, and the copper paste printing hole 34 is reserved to facilitate the coating of the copper paste slurry 5 at the specified position. The upper substrate 22 and the lower substrate 21 are copper blocks with copper surfaces, simulating a chip with a copper layer on the bottom and a DBC substrate with a copper layer on the top, to achieve full copper packaging.
[0058] Among them, in step three, the fixture 6 is designed using modeling software, and the modeling software can be CAD or the like.
[0059] Among them, in step four, the interconnected sample 2 is placed in the upper clamp 61 and the lower clamp 62. The upper clamp 61 and the lower clamp 62 are stainless steel round blocks. After the stainless steel bolts 81 pass through the through holes around the round blocks, pressure is applied by the upper spring 7, and finally fixed by the bolts 81 and nuts 82.
[0060] Among them, step five performs oxidation sintering in the sintering furnace cavity, and the gas in the cavity is air.
[0061] Among them, in step six, the air is first removed from the sintering furnace cavity, and then a reducing gas is introduced to perform reduction sintering. The gas in the cavity is a reducing gas, and the reducing gas is formic acid gas.
[0062] Among them, in step seven, the cooling rate and cooling time are controlled to make the experiment stable.
[0063] like Fig.10 As shown, an embodiment of the second aspect of the present invention provides an electronic device 1, including an interconnection sample 2, wherein the interconnection sample 2 is prepared by the redox sintering method of the copper paste-based interconnection sample provided by any embodiment of the first aspect of the present invention.
[0064] Since the electronic device 1 provided by the present invention includes the interconnection sample 2, and the interconnection sample 2 is prepared by the redox sintering method of the interconnection sample based on copper paste provided by any embodiment of the first aspect, the electronic device 1 of the present invention has all the beneficial effects of the redox sintering method of the interconnection sample based on copper paste provided by any embodiment of the first aspect of the present invention.
[0065] In the embodiments according to the present invention, the terms "first", "second", and "third" are only used for description and cannot be understood as indicating or implying relative importance; the term "plurality" refers to two or more, unless otherwise clearly defined. The terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense. For example, "connected" can be a fixed connection, a detachable connection, or an integral connection; "connected" can be a direct connection or an indirect connection through an intermediate medium. For those of ordinary skill in the art, the specific meanings of the above terms in the embodiments according to the present invention can be understood according to specific circumstances.
[0066] In addition, although each operation is described in a specific order, this should be understood as requiring such operation to be performed in a specific order or in a sequential order, or requiring that all illustrated operations should be performed to obtain desired results. Under certain circumstances, multitasking and parallel processing may be advantageous. Similarly, although some specific implementation details are included in the above discussion, these should not be interpreted as limiting the scope of the present invention. Some features described in the context of a separate embodiment can also be implemented in a single implementation in combination. On the contrary, the various features described in the context of a single implementation can also be implemented in multiple implementations individually or in any suitable sub-combination mode.
[0067] Although the subject matter has been described in the language of specific structural features and / or method logical actions, it should be understood that the subject matter defined in the appended claims is not necessarily limited to the specific features or actions described above. On the contrary, the specific features and actions described above are merely example forms of implementing the claims.
[0068] The above are only preferred embodiments according to the embodiments of the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, various modifications and changes may be made according to the embodiments of the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the embodiments of the present invention shall be included in the protection scope of the embodiments of the present invention.
Claims
1. A redox sintering method for interconnection samples based on copper paste, characterized in that: include: Dissolving the raw materials of the copper paste in an organic solvent to obtain a copper paste slurry; Prepare an interconnection sample by using an upper substrate, a lower substrate and the copper paste slurry; applying pressure to the interconnection sample on the upper substrate toward the lower substrate; Heating the interconnected sample under pressure at a first preset rate, maintaining the temperature for a first preset time after reaching the first preset temperature, and then cooling the interconnected sample to room temperature; In a reducing gas environment, the interconnected sample at room temperature is heated at a second preset rate, and after reaching the second preset temperature, it is kept warm for a second preset time. Then, the temperature is heated at a third preset rate, and after reaching the third preset temperature, it is kept warm for a third preset time.
2. The redox sintering method of the interconnection sample based on copper paste according to claim 1, characterized in that: The raw materials of the copper paste include micron-sized copper particles and nano-sized copper particles. The diameter of the micron-sized copper particles is greater than or equal to 1 μm and less than or equal to 100 μm, and the diameter of the nano-sized copper particles is greater than or equal to 1 nm and less than or equal to 100 nm.
3. The redox sintering method of the interconnection sample based on copper paste according to claim 2, characterized in that: The mass ratio of the micron-sized copper particles to the nano-sized copper particles is greater than or equal to 3 and less than or equal to 5.
4. The redox sintering method of the interconnection sample based on copper paste according to claim 1, characterized in that: The step of preparing an interconnection sample by using an upper substrate, a lower substrate and the copper paste slurry comprises: The lower substrate is positioned, the copper paste slurry is brushed onto the upper surface of the lower substrate, and then the upper substrate is placed on the copper paste slurry to obtain the interconnection sample.
5. The redox sintering method of the interconnection sample based on copper paste according to claim 1, characterized in that: The step of applying pressure to the interconnected sample specifically comprises: The interconnect sample is placed in a jig, and pressure is applied to the interconnect sample by the jig.
6. The redox sintering method of the interconnection sample based on copper paste according to claim 1, characterized in that: In the step of applying pressure to the interconnection sample, the applied pressure is greater than or equal to 100N and less than or equal to 1000N.
7. The redox sintering method of the interconnection sample based on copper paste according to claim 1, characterized in that: The first preset rate is greater than or equal to 1°C / s and less than or equal to 2°C / s; The first preset temperature is greater than or equal to 280° C. and less than or equal to 320° C.; The first preset duration is less than or equal to 40 minutes; The second preset rate is greater than or equal to 1°C / s and less than or equal to 2°C / s; The second preset temperature is greater than or equal to 25° C. and less than or equal to 35° C.; The second preset duration is greater than or equal to 20 minutes and less than or equal to 2 hours; The third preset rate is greater than or equal to 1°C / s and less than or equal to 2°C / s; The third preset temperature is greater than or equal to 200° C. and less than or equal to 300° C.; The third preset duration is less than or equal to 20 minutes.
8. The redox sintering method of the copper paste-based interconnection sample according to claim 1, characterized in that: The reducing gas includes formic acid gas.
9. The redox sintering method of the copper paste-based interconnection sample according to claim 1, characterized in that: Also includes: After the third preset time period, cooling the interconnected sample to a fourth preset temperature at a fourth preset rate; The fourth preset rate is greater than or equal to 1°C / s and less than or equal to 2°C / s, and the fourth preset temperature is greater than or equal to 30°C and less than or equal to 50°C.
10. The redox sintering method of the interconnection sample based on copper paste according to claim 1, characterized in that: The organic solvent includes terpineol.
11. An electronic device, characterized in that: include: An interconnection sample is prepared by the redox sintering method of the copper paste-based interconnection sample according to any one of claims 1 to 10.